Nilai Ekologi dalam Kearifan Lokal Masyarakat Muslim Minangkabau: Tinjauan atas Legenda Bujang Sembilan dan Tradisi Lubuk Larangan - Irfan S. Berutu; Asep Ahmad Hidayat (KURAS Institute, 2023)
The ecology review in connection with culture is a topic that must be mainstreamed in the current era. Culture is alleged to have a significant contribution to protecting nature. This article aims to discuss the value of ecology in the local wisdom of the Minangkabau Muslim community in the form of the Legend of Bujang Sembilan and the Lubuk Larangan Tradition. This article uses qualitative library research with descriptive inductive analysis. Data were collected from various books and relevant journal articles. The results of this study indicate that moral and social values are present in the Legend of Bujang Sembilan. Moral and social values encourage people to work together to protect nature and each other. In the Lubuk Larangan tradition, ecological values help protect fish populations and river ecosystems, increase community economic income, and preserve hereditary culture. The Lubuk Larangan tradition contains noble national character values such as caring for the environment, social care, and discipline to existing rules. Thus, the tradition is used as a reference for understanding the community to preserve nature and positively impact society.